TREASURE OF THE COPPER SCROLL - Allegro, John Marco, 1923- author. ([S.l.])
1 online resource.
Keywords: First published in 1960, The Treasure of the Copper Scroll is the companion volume to John Marco Allegro's People of the Dead Sea Scrolls and tells the story of this unusual, buried treasure. Allegro here reveals much hitherto unknown information - the location of many of the cities of the Old Testament, events of the second Jewish Revolt, and the relation between the Essene community at Qumran and the New Testament interest in healing. With facsimiles of the scroll, translations of its texts, and a thorough discussion of its significance, with maps indicating many of the probable present-day hiding places, the book is a truly fascinating report on this unusual document and a first long step toward the unravelling of its secrets.